Tomasz M. Dąbek OSB, Modlić się Psalmami, Wydawnictwo Benedyktynów, Tyniec–Kraków, 2019, ss. 98 - Ćwikła, Jarosław (Poznańskie Studia Teologiczne, 2021)
The Book of Psalms is one of the most popular and most read Bible books. For over 2,000 years, both Jews and Christians — including Catholics, Protestants and Orthodox Christians — have been reading it. It is worth emphasizing, however, that this is not an easy book. It was created in a culture foreign to us, in a foreign language (Hebrew — biblical) — it was written by people with a different mentality than ours. Therefor to understand it, you need the right knowledge. Unfortunately, this can only be obtained at theological faculties. It is known, however, that not all Bible readers feel called to study theology. Many exegetes understand this and write comments for them on Bible books, including the Book of Psalms. One of these exegetes is Fr. professor Tomasz M. Dąbek, the author of the book: To pray with Psalms, which was published in 2019 in Tyniec–Krakow. He divided his dissertation into several parts, which he titled: Introduction (pp. 7–8), Psalter as a prayer book of the People of God of the First Covenant (pp. 9–44), Psalms in the New Testament (pp. 45–58), Psalter as a prayer book to monks, consecrated persons and clergy (pp. 59–68), Psalter in the liturgy and in the personal prayer of a Christian (pp. 69–74), Thoughts about some Psalms (pp. 75–94), Summary (pp. 95–96) and Bibliographic proposals (pp. 97–98). This review presents his book.